Unit Cost Analysis of Sterile Surgical Drape Pack Production for the Operating Rooms at Srinagarind Hospital, Faculty of Medicine, Khon Kaen University. - Ruangprasertkul, Sasithorn; Riratanapong, Saowaluck; Iamthong, Chatarat; Ubhadip, Pakamon; Nontapa, Pikul; Kingwong, Runchida (Srinagarind Medical Journal, 2020)
Background and Objective: Healthcare institutions can improve administration through effective cost management. This study aimed to evaluate the production cost of in-house sterile surgical drape packs at Srinagarind hospital, Faculty of Medicine, Khon Kaen university, and compare to the prices of externally procured counterparts. Methods: The descriptive study was conducted as follows: 1) analyzing workflow of hospital units related to the production of sterile surgical packs; 2) determining the components of economic and accounting costs of in-house surgical packs; 3) calculating the direct cost of surgical pack production based on labors, supplies, infrastructure, and maintenance; and 4) determining the cost per unit for each type of the packs, and for each type of procedure. Results: Among 27 types of surgical drape packs, unit cost ranged from 26.81 to 192.11 baht, with the average of 100.31 baht. The results showed that the cost of in-house sterile surgical drape packs varied from 405 to 909 baht, averaging 549 baht per procedure, while the cost of an outsourced drape pack averaged 2,191 baht, with prices falling between 1,855 to 2,404 baht in the same case scenario. For the same type of procedure, the cost for outsourced surgical pack(s) is two to five times higher than that of using in-house products. Conclusion: The cost of in-house sterile surgical drape pack production at Srinagarind hospital is lower than the cost of outsourcing equivalent products.